2022
DOI: 10.2196/40572
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Measuring Screen Time, Activity, and Context Among Families With Preschoolers: Intensive Longitudinal Pilot Study

Abstract: Background Digital media has made screen time more available across multiple contexts, but our understanding of the ways children and families use digital media has lagged behind the rapid adoption of this technology. Objective This study evaluated the feasibility of an intensive longitudinal data collection protocol to objectively measure digital media use, physical activity, sleep, sedentary behavior, and socioemotional context among caregiver-child d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Specifically with the passive-sensing application Chronicle, data are not associated with IP addresses or phone numbers and only indicate the type of application used (e.g., educational, social media), not the information on websites visited or the content of messages and emails. Parents are comfortable with using passive sensing technology when participating in a research study, as indicated by a feasibility study reporting no dropouts due to privacy concerns in using this technology [ 171 ]. While passive sensing applications have been shown to be accepted for use by families, future research can examine the extent to which families are comfortable with sensor tracking technology (e.g., accelerometer, gyroscope, touch) continuously monitoring user behavior on shared mobile devices.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically with the passive-sensing application Chronicle, data are not associated with IP addresses or phone numbers and only indicate the type of application used (e.g., educational, social media), not the information on websites visited or the content of messages and emails. Parents are comfortable with using passive sensing technology when participating in a research study, as indicated by a feasibility study reporting no dropouts due to privacy concerns in using this technology [ 171 ]. While passive sensing applications have been shown to be accepted for use by families, future research can examine the extent to which families are comfortable with sensor tracking technology (e.g., accelerometer, gyroscope, touch) continuously monitoring user behavior on shared mobile devices.…”
Section: Discussionmentioning
confidence: 99%
“…While child or parent self-report and parent proxy-report have been the most common methods of assessment in research to date, studies of self-report of screen use suggest low validity (Boase & Ling, 2013), where adults tend to under-report their use of television (Clark et al, 2009) and smartphones (Lee et al, 2017). Recent studies of parents suggest there is poor correspondence between caregiver self-report and objective measures of child and parent screen use (Barr et al, 2020;Parker et al, 2022;Radesky et al, 2020). Current work on objective measures of screen use holds promise in terms of obtaining more accurate measures of child exposure (e.g., Radesky et al, 2020;Vadathya et al, 2022), however, given the number of devices a child may access in the home and in the community, both actively and passively, the task of estimating screen exposure is complex.…”
Section: Assessment Of Screen Usementioning
confidence: 99%